Long-term effects of acoustic reafference training (ART) - Pizzera, Alexandra (European journal of sport science, 2017)
In sport visual feedback is often used to enhance performance, mostly neglecting the auditory modality. However, athletes produce natural sounds when they move (acoustic reafferences) which they perceive and use to control their movements. We examined the short- and long-term effects of a training intervention on a complex movement by using acoustic reafferences. Natural step sounds produced during hurdling were recorded and played back to the participants immediately before each trial, with an increase (fast group), decrease (slow group), or no manipulation (control group) in the tempo. All groups increased their hurdling performance regarding overall running time, with the slow group showing the best performance development. After a 10-week retention, the fast and slow group further increased performance, whereas the control group declined. The repeated experience with acoustic information associated with the rhythmic pattern of hurdling may have helped developing a cognitive representation of that movement, especially regarding long-term effects.